The Pilling-Bedworth Ratio of Oxides Formed From the Precipitated Phases in Magnesium Alloys - Jiang, Quantong; Lu, Dongzhu; Liu, Chang; Liu, Nazhen; Hou, Baorong (Frontiers in Materials, 2021)
The Pilling-Bedworth ratio of oxides preferentially formed from the precipitated phases in magnesium alloys were calculated. The results showed that the PBR value of Nd2O3 preferentially formed from Mg12Nd was 1.0584, and the PBR value of Y2O3 preferentially formed from Mg24Y5 was 1.1923. Both the Nd2O3 and Y2O3 would provide a good protection to the Mg matrix. The Gd2O3 preferentially formed from Mg3Gd, whereas the MgO preferentially formed from MgNi2. The PBR value of these two oxides were both larger than 2. The corresponding oxides formed from the common precipitated phases Mg17Al12, MgZn2, MgCu2, Mg2Ca, Mg12Ce, and MgAg were all less than 1. The oxide films formed on surfaces of pure Mg and Mg-xY (x=3, 5, 7 wt.%) alloys at high temperatures were analyzed. The results showed that the oxide films were composed of a Y2O3/MgO outer layer and an inner layer rich with Y2O3. The formation of Y2O3 was mainly caused by the oxidation of Mg24Y5. The more Y2O3 existed in the composite oxidation film, the better corrosion resistance of the Mg-Y samples.